1996
DOI: 10.1007/bf02087925
|View full text |Cite
|
Sign up to set email alerts
|

Circulating intercellular adhesion molecule-1 (ICAM-1) in patients with hepatolithiasis

Abstract: We evaluated the role of circulating intercellular adhesion molecule-1 in the pathogenesis of hepatolithiasis. From December 1994 to May 1995, 40 patients with hepatolithiasis were included. All the patients met the following criteria: (1) presence of hepatolithiasis, (2) no obvious clinical evidence of an associated intrahepatic cholangiocarcinoma, (3) no clinical manifestation of cholangitis for at least 72 hr, (4) no immunomodulatory agents in the last three weeks, and (5) no blood transfusion in the last t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Sheen-Chen et al . showed a similar relationship [17]. Byrne described a statistically significant increase in the concentration of sVCAM-1 levels in breast cancer patients who developed metastases in comparison to those in whom metastases were not present [14].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Sheen-Chen et al . showed a similar relationship [17]. Byrne described a statistically significant increase in the concentration of sVCAM-1 levels in breast cancer patients who developed metastases in comparison to those in whom metastases were not present [14].…”
Section: Discussionmentioning
confidence: 90%
“…The studies demonstrated a significant increase in the concentration of the studied adhesion molecules in patients suffering from this cancer in comparison to the control group. Similar observations were made by Sheen-Chen et al ., who observed a statistically significant increase in the concentration of sICAM-1 in the serum of patients with invasive breast cancer [ 17 ]. Similarly, Madej and O'Hanlon, in their study, showed elevated levels of adhesion molecules in the serum of patients with breast cancer [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some cell surface adhesion molecules, such as leukocyte functioning antigen (LFA)‐3, human leukocyte antigen (HLA)‐I and HLA‐II, are expressed in normal human cholangiocytes as demonstrated by both in vivo and in vitro studies 57 , 58 , 59 . Enhanced expression of adhesion molecules on cholangiocytes has been demonstrated in several inflammatory hepatobiliary diseases including primary biliary cirrhosis, primary sclerosing cholangitis and hepatolithiasis 60 , 61 . Additionally, microbial infection in the biliary system is usually associated with an enhanced expression of adhesion molecules on cholangiocytes.…”
Section: Activation Of Cholangiocyte Immune Responsesmentioning
confidence: 99%
“…[57][58][59] Enhanced expression of adhesion molecules on cholangiocytes has been demonstrated in several inflammatory hepatobiliary diseases including primary biliary cirrhosis, primary sclerosing cholangitis and hepatolithiasis. 60,61 Additionally, microbial infection in the biliary system is usually associated with an enhanced expression of adhesion molecules on cholangiocytes. Expression of HLA-I on cultured human cholangiocytes was increased after infection with the cytomegalovirus.…”
Section: Expression Of Adhesion Moleculesmentioning
confidence: 99%
“…In einer taiwanesischen Untersuchung wurden bei allen Patienten bakterielle Erreger in der Galleflu È ssigkeit nachgewiesen [3], die mit einer Ønderung der Gallezusammensetzung wie dem Auftreten des zirkulierenden interzellula È ren Adha È sionsmoleku È ls assoziiert waren. Andererseits spielen auch die genetische Pra È disposition [2], Anomalien der Gallenwege (insbesondere Stenosen) und mo È glicherweise die Erna Èhrung eine Rolle [1,4].…”
unclassified